Program Makan Siang Gratis; School Efforts to Improve Learning Concentration and Academic Achievement - Fathor Rozi; Laila Misbahatul Mukarromah (PALAPA, 2025)
Poor nutritional conditions in elementary school students can hinder the learning process and have an impact on decreasing concentration and academic achievement. This study was motivated by this phenomenon, especially at SDN 1 Karanggeger, where many students come to school without adequate nutritional intake. The purpose of this study was to analyze the effectiveness of the free lunch program in improving students' concentration and academic achievement. This study used a qualitative approach with a case study method, involving observation, in-depth interviews, and documentation as data collection techniques. The results showed that the free lunch program contributed positively to increasing student attendance, focus on learning in class, involvement in discussions, and the ability to complete academic tasks. Students' average academic grades also increased significantly after the program was implemented. The program also created a more conducive learning environment and increased students' motivation and social interaction. The implications of this study are very relevant to education policy, especially in areas with economic constraints, because they show that nutrition-based interventions can be an effective strategy in improving the quality of education. It is recommended that similar programs be implemented more widely and accompanied by monitoring and nutrition education for students and parents to ensure the sustainability of their benefits.